MRI Radiomics in Prostate Cancer: A Reliability Study - Urraro, Fabrizio; Nardone, Valerio; Reginelli, Alfonso; Varelli, Carlo; Angrisani, Antonio; Patanè, Vittorio; D’Ambrosio, Luca; Roccatagliata, Pietro; Russo, Gaetano Maria; Gallo, Luigi; De Chiara, Marco; Altucci, Lucia; et al. (Frontiers in Oncology, 2021)
Background Radiomics can provide quantitative features from medical imaging that can be correlated to clinical endpoints. The challenges relevant to robustness of radiomics features has been analyzed by many researchers, as it seems to be influenced by acquisition and reconstruction protocols, as well as by the segmentation of the region of interest (ROI). Prostate cancer (PCa) represents a difficult playground for this technique, due to the discrepancies in identification of the cancer lesion and the heterogeneity of the acquisition protocols. Aim of this study is to investigate the reliability of radiomics in PCa Magnetic Risonance Imaging (MRI). Methods A homogeneous cohort of patients with a PSA rise that underwent multiparametric MRI imaging of the prostate before biopsy was tested in this study. All the patients were acquired with the same MRI scanner, with a standardized protocol. The identification and the contouring of region of interest (ROI) of a MRI suspicious cancer lesion was done by two Radiologist with great experience in prostate cancer (>10 years). After the segmentation, texture features were extracted with LifeX. Texture features were then tested with intraclass coefficient correlation (ICC) analysis to analyse the reliability of the segmentation. Results Forty-four consecutive patients were included in the present analysis. In 26 patients (59,1%) the prostate biopsy confirmed the presence of prostate cancer, that was scored as Gleason 6 in 6 patients (13,6%), Gleason 3+4 in 8 patients (18,2) and Gleason 4+3 in 12 patients (27.3%). The reliability analysis, conversely, showed poor reliability in the majority of the MRI acquisition (61% in T2, 89% in DWI50, 44% in DWI400 and 83% in DWI1500), with ADC acquisition only showing better reliability (poor reliability in only 33% of the texture features). Conclusions The low ratio of reliability in a monoinstitutional homogenous represents a significant alarm bell for the application of MRI Radiomics in the field of prostate cancer. More work is needed in a clinical setting to further study the potential of MRI radiomics in prostate cancer.